GREEN LOGISTICS AND ENVIRONMENTAL SUSTAINABILITY - Shahnoz Bebudovna Boltayeva; Tohirova Dilroz Shermat qizi (Modern American Journals, 2026)
Green logistics has become an essential component of modern supply chain management as global concerns about environmental degradation and climate change continue to grow. This article examines the concept of green logistics and its role in promoting environmental sustainability. It focuses on environmentally friendly transportation, efficient resource utilization, waste reduction, and the adoption of eco-friendly technologies in logistics processes. The study highlights how green logistics practices help reduce carbon emissions, minimize environmental impact, and support sustainable economic development. Additionally, the article discusses the challenges and future prospects of implementing green logistics strategies in developing and developed economies. The findings emphasize that integrating green logistics into supply chains is crucial for achieving long-term ecological balance and sustainable growth.
Keywords: Green logistics, environmental sustainability, sustainable supply chain, eco-friendly transportation, carbon emission reduction, resource efficiency, waste management, green technology.